Mary Stuart - Mulvany, Kate (Currency plays., 2020)
Kate Mulvany's smart and witty adaptation of Friedrich Schiller's Mary Stuart is a tale of two queens at war. In the legendary rivalry between Elizabeth I and Mary Stuart, great forces are at play, with nations at stake and citizens ready to fight for the just cause. On the one hand there is principle and ideology; on the other, jealousy and pride. But there is also love. For who else could understand what torments a queen better than another queen? Mulvany turns her feminist lens on this brutal and moving story of cousins pitted against each other by politics and circumstance, trapped on diff.